Hubungan Senam Hamil dengan Nyeri Punggung Pada Ibu Hamil Trimester III - Miratu Megasari (STIKes Hang Tuah Pekanbaru, 2015)
Low back pain is one of the discomfort which often occurred during pregnancy. Lowback pain is a condition experienced by many pregnant women throughout pregnancy period to the post-delivery period. One of the solutions to address this issue is by doing exercise for pregnancy women.The study was conducted to find out the effect of pregnancy exercisesto reduce low back pain issue. The data source is pregnant women on their third quarter of pregnancy period in Fatmawati’s private clinic during 28th February 2015 until 31 March 2015. This is aquantitative analysis study. The number of samples are 89 pregnant women and 47 out of them are choosen by accidental sampling technique. Primary data in this study has been analyzed using chi square statistical test. The result of this study showed that p value = 0.000; which is p value which is smaller than α ( 0.05 ). It indicated that there is a significant effect of pregnancy exercises to reduce low back pain issue. Statistical test result showed that the OR (Odds Ratio) value = 2.600, which mean that pregnant women who did not take pregnancy exercises have likelihood to suffer from low back pain 3 times higher than pregnant women who took it. In brief, it can be seen that pregnancy exercise can be a solution to solve the low back pain issue during pregnancy period.